Agriculture and Crop Management in the Ninevite V Culture. - Fattah, Othman Tawfeeq; Ahmed, Kozad Muhammad (Journal of University of Human Development, 2024)
Ninevit V culture is the culture that spread across most of the land of (southern, northern and western of present-day Kurdistan) in the early 3rd millennium BC. and lasted for 500 years. Despite some environmental challenges such as low rainfall, agriculture and administration of its products، the two most important economic sources of Ninevit V community at that time. This article which is part of a doctoral dissertation on Ninevite V culture، seeks to identify these two important aspects of society’s life. It divided into two parts، the first being the cultivation and how Ninevite V community was trying to increase their agricultural output. The second part: focuses on the management of agriculture and grain storages. It’s about how to build silos and store crops.